Researching multilingualism critical and ethnographic perspectives - Martin-Jones, Marilyn; Martin, Deirdre (Routledge, Taylor & Francis Group, 2017)
Researching Multilingualism" expertly engages with a new sociolinguistics of multilingualism, taking account of this new communicative order and the particular cultural and social conditions of our times. Seventeen chapters are divided into four sections covering: researching discourses, policies and practices; contemporary mobilities; Researching multilingual communication on-line; Multilingualism in research practice. This state-of-the-art overview of research methodologies in multilingual settings will be of interest for all students and researchers working in the area of multilingualism within Linguistics, Applied Linguistics, Education and Communication Studies